Determining economic productivity under environmental and resource pressures: An empirical application - Christina Bampatsou; George Halkos; Andreas Dimou (Journal of Economic Structures, 2017)
The current study is divided into two parts. Part I deals with the indices of resource and impact decoupling for 13 countries of the EU, for a period spanning from 1990 to 2011. Employing the major pressures, of GHG emissions, mineral resource extraction and land use, the different cases of relative/absolute and no decoupling are determined. Part II uses data envelopment analysis to determine the resource productivity index on the basis of the same sample of countries, over the same period of time. Resource productivity index attempts to quantify the simultaneous application and the interrelationships of decoupling indices. The index of the GDP is used as output, while the indices of material resources, land resources and GHG emissions are used as inputs. Then, the index of total factor productivity changes is decomposed into efficiency change and technical change, showing, respectively, whether the productivity gains come mainly from improvements in efficiency or are mainly the result of technological progress. Finally, the index of efficiency change is decomposed into pure efficiency and scale efficiency, showing, respectively, whether the major source of efficiency change comes mainly from improvements in pure technical efficiency or is mainly the result of an improvement in scale efficiency.
Keywords: 330; Data envelopment analysis; Productivity; Decoupling index; Material resources; Land resources; GHG emissions; Economic growth; Elasticity